A study of visual inspection of cervix under acetic acid and visual inspection of cervix under Lugol's iodine for screening of carcinoma cervix - Kanash, Sunita; Shirodkar, S. D.; Gawai, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Carcinoma cervix is the most common cancer among women in developing countries. The objectives of the study were to study the sensitivity and specificity of visual inspection of the cervix with acetic acid (VIA) and Lugol's iodine (VILI) for cervical cancer screening. To study the correlation of demographic data like age, socioeconomic status, education residential area, parity, age at marriage in premalignant lesion of the cervix. Methods: The present study was conducted in the department of Obstetrics and Gynecology at a Tertiary Medical Care Center over a period of two years. Five hundred fifty women between 20-65 years of age who fulfilled the selection criteria were enrolled in our study. Positive tests for VIA was opaque aceto white lesion on applying 5% acetic acid or detection of definite yellow iodine non uptake areas with Lugol's iodine in the transformation zone or close to touching the squamocolumnar junction. Positive cases were scheduled for cervical biopsy. Ethical approval of the study protocol was obtained from the ethics committee of the institute. Results: On down staging 7.2% (40/550) of cases had an unhealthy cervix and 0.36% (2/550) with a suspicious cervix. VIA positive in 4.55% (25/550), VILI positive in 2.73% (15/550). Biopsy was taken from positive with VIA and VILI. On histology 2.9% (16) were chronic cervicitis, CIN I had (1), 0.2%, CIN II (2) 0.4%, CIN III (4) 0.7% and squamous cell carcinoma (2) 0.4% VIA sensitivity 72.22%, specificity 97.74%. VILI sensitivity 100%, specificity 98.89%. Conclusions: VIA and VILI are simple, inexpensive, low resources technique. Both have high sensitivity and specificity.